Prescribing patterns and cost analysis of anti glaucoma medications in a tertiary care teaching hospital - Elfride Farokh, Sanjana; Kishore Sastha, Ram V.; Philip, Serin (International Journal of Medical Research and Review, 2016)
Aim: To study the prescribing patterns and cost analysis of anti glaucoma medications in a tertiary care teaching hospital. Materials and Methods: This was a prospective study conducted in 62 patients of either sex who presented in the Department of Ophthalmology with an established diagnosis of glaucoma as per Asia Pacific Glaucoma Guidelines (SEAGIG). A specially designed proforma was used to collect data. Visual acuity with and without correction, intraocular pressure measurement with applanation tonometer which was corrected with pachymetry, stereoscopic evaluation of optic nerve head and Humphrey visual analysis was done to establish the diagnosis of glaucoma. All prescriptions were analyzed for the nature of drugs prescribed, percentage of prescriptions that included mono therapy versus fixed dose combinations, the preferred regimen chosen and switch over amongst the various classes. Results: The incidence of glaucoma was maximum in the 5th -6th decades of life. Mean age was 58+/_ 13.781, with males 63% and females 11.29%. Both eyes were affected in 49(79.03%) of patients. Risk factors were identified commonly diabetes mellitus and hypertension. Thirty (50%) of patients were on beta blockers, followed by prostaglandin analogues 13(21.6%) and fixed dosed combinations comprising 12(20%) and alpha agonists 5(8.33%). The cost per bottle of monotherapy and fixed drug combinations was analyzed and beta blockers were the most economical drugs in the management of glaucoma. Conclusion: Beta blockers remained the first drug of choice followed by prostaglandin analogues. No patient had clinically significant ocular or systemic side effects from beta blockers and it continues to remain a suitable economical option in patients with socioeconomic constraints in contrast to the Western world literature that choses prostaglandin analogue over beta blockers.